2016
DOI: 10.1111/gcb.13530
|View full text |Cite
|
Sign up to set email alerts
|

Hot spots of wheat yield decline with rising temperatures

Abstract: Many of the irrigated spring wheat regions in the world are also regions with high poverty. The impacts of temperature increase on wheat yield in regions of high poverty are uncertain. A grain yield-temperature response function combined with a quantification of model uncertainty was constructed using a multimodel ensemble from two key irrigated spring wheat areas (India and Sudan) and applied to all irrigated spring wheat regions in the world. Southern Indian and southern Pakistani wheat-growing regions with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 40 publications
5
52
1
1
Order By: Relevance
“…From Table 3, the DER of the tablets generally increased with increase in the concentration of cassava starch. This observation is in agreement with the results of a recent study in Nigeria [18]. The rank order of the DER values of tablets containing cassava starch was V40 > V50 > V20 > V60 > V30 >V10.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…From Table 3, the DER of the tablets generally increased with increase in the concentration of cassava starch. This observation is in agreement with the results of a recent study in Nigeria [18]. The rank order of the DER values of tablets containing cassava starch was V40 > V50 > V20 > V60 > V30 >V10.…”
Section: Resultssupporting
confidence: 92%
“…Cassava starch yield was affected by the cassava variety used. Other factors which are known to affect cassava starch yield include processing factors [16], the extraction method employed [17], and the season of harvest of the cassava crop [18]. The cassava starches were white in colour and odourless and had characteristic fine texture and bland taste which complied with the official organoleptic tests for starch [9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our multistress analysis confirmed that heat stress is particularly important in this region (Lobell, Sibley, & Ortiz‐Monasterio, ). Site‐specific analysis of the effects of future increases in temperature in 2030–2040 indicated that heat stress is likely to continue to reduce yields in the Indo‐Gangetic Plain, especially under climate change (Asseng, Cammarano, & Basso, ). Given that from a food security perspective, it is crucial to reduce yield gaps in India, reducing ozone pollution and/or its effects could potentially provide beneficial additional yield in future climates.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we address this knowledge gap by developing multiple statistical crop yield models for wheat and rice production in India using 50 unique combinations of weather datasets. Our study focuses on India due to the availability of comprehensive historical yield observation data, along with the widespread past use of statistical modelling approaches in India and South Asia as part of climate impact resear-ch (Lobell et al 2012, Duncan et al 2015, 2016, Asseng et al 2017, Jain et al 2017, Gilmont et al 2018. We hypothesise that weather dataset choice will have an impact on estimates of crop yield responses to weather shocks.…”
Section: Introductionmentioning
confidence: 99%